Searches for cosmic-ray electron anisotropies with the Fermi Large Area Telescope - Ackermann, Markus; Ajello, Marco; Atwood, W. B.; Baldini, Luca; Ballet, J.; Barbiellini, G.; Bastieri, Denis; Bechtol, K.; Bellazzini, R.; Berenji, Bijan; Bloom, E. D.; Bonamente, E.; et al. (Physical Review D, 2010)
The Large Area Telescope on board the Fermi satellite (Fermi LAT) detected more than 1.6 x 10(6) cosmic-ray electrons/positrons with energies above 60 GeV during its first year of operation. The arrival directions of these events were searched for anisotropies of angular scale extending from similar to 10 degrees up to 90 degrees, and of minimum energy extending from 60 GeV up to 480 GeV. Two independent techniques were used to search for anisotropies, both resulting in null results. Upper limits on the degree of the anisotropy were set that depended on the analyzed energy range and on the anisotropy's angular scale. The upper limits for a dipole anisotropy ranged from similar to 0.5% to similar to 10%.
CRIS-Team WoS Importer:2020-01-15